PENINGKATAN HASIL BELAJAR BIOLOGI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) - Fitra Halimah Nasution; Iskandar Safri Hasibuan; Jalilah Azizah Lubis (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2017)
The results can be seen from the test results of student learning on Ecosystem materials are characterized by the level of student learning mastery. In cycle I with an average value of 78.10 and in cycle II with an average value of 84.48. From the average value ofcycleIandcycle II there is an average increase of 13.25. The percentage value in cycle I is 72,41% with enough qualification. And the percentage in cycle II equal to 86,20% with very good qualification. From the results of the test cycle I and cycle II has been an increase in percentage of 13.79%. Student learning activities increase by using the GI learning model. The value of activity percentage in cycle I is 69,4% with enough qualification. In the second cycle of 80.9% with very good qualifications. From the results of student learning activities in cycle I and in cycle II has been an increase in thepercentage of 11.5%. Based on the results of this study, it can be concluded that there is an increase in student biology learning outcomes through cooperative learning model type Group Investigation (GI) on Ecosystem material in class X MA. Muhammadiyah 06 Kotanopan as prescribed in the action hypothesis in Chapter II so that the hypothesis of this action is acceptable. Keywords:Learning Outcomes, Application of Cooperative Learning Model Type Group Investigation (GI), Ecosystem.